Study material on Parliamentary practices and procedures - Lok Sabha Srcretariat (New Delhi, 2015)
This book cover following topics Parliamentary questions, Procedural devices for raising matters of urgent public importance, Legislative process, Budgetary process and Committee system in India.
Keywords: Legislative Rules and Procedure